2019
DOI: 10.1021/acs.jpcc.9b05069
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation vs Solution Sequential Doping of Conjugated Polymers: F4TCNQ Doping of Micrometer-Thick P3HT Films for Thermoelectrics

Abstract: For thermoelectric and other device applications there has been great interest in the chemical doping of conjugated polymer films. Solution doping followed by film deposition generally produces poor-quality films, but this issue can be alleviated by sequential doping: a pure polymer film is deposited first, and the dopant is then added as a second processing step, preserving the quality and structure of the original polymer film. In this paper, we compare two methods for sequential doping of conjugated polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 73 publications
3
76
0
Order By: Relevance
“…1 dopant per 5 rings), which is consistent with previous P3HT-F4TCNQ reports. 30,31 Inspection of the N-1s spectra shown in Figure 2e provides additional insight as Watts et al…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…1 dopant per 5 rings), which is consistent with previous P3HT-F4TCNQ reports. 30,31 Inspection of the N-1s spectra shown in Figure 2e provides additional insight as Watts et al…”
mentioning
confidence: 79%
“…Vapor doped films were chosen because it has been demonstrated that this maintains higher degrees of structural ordering compared to solution doped films, and we observe comparable spectroscopic properties with both types of doping. 26,30 A brief discussion of the pristine GIWAXS scattering shown in Figure 3a-c can be found in Note S5. Upon doping with F4TCNQ in the vapor phase, a clear change in the scattering pattern occurs for all the polymers (Figure 3d-f).…”
mentioning
confidence: 99%
“…Interestingly, for all the DDB dopants, we see coexistence of doped and undoped phases over a broad range of dopant concentrations. This is not observed with F 4 TCNQ, where minimal amounts of dopant appear to induce a phase transition in nearly all regions of the film at once, [24] and then F 4 TCNQ continues to add to and "fill up" those transformed crystallites. [25] By contrast, with the DDB clusters, the structural change is so extreme that "partially filled" but expanded crystallites are more energetically favorable.…”
Section: Local Structure Of Ddb-doped P3ht Filmsmentioning
confidence: 92%
“…[6,16,[30][31][32] A dominant idea in the literature has been that highly crystalline polymer films are necessary to achieve good charge transport properties, with many molecular doping papers focusing on improving polymer solid state order. [5,16,[20][21][22][23][24]31] In a previous work, we showed that we could use solution SqP to control the crystallinity of doped conjugated polymer films. [5] For the widely used poly(3-hexylthiophene-2,5-diyl) (P3HT) and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F 4 TCNQ) materials combination, we indeed found higher carrier mobilities in more crystalline films.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Sequential doping avoids possible complications that arise if the doped material is poorly soluble in the casting solvent and in some cases may allow for the preservation of some of the structural order present in the pristine semiconductor film. Although widely applied to the p-doping of P3HT [5][6][7][8] and PBTTT, 9,10 there are only few reports of the sequential n-doping of solution-processed polymers. 11 The air-stability of oxidants, hole-transport materials, and their doped combinations often allow for easy handling in air.…”
Section: Introductionmentioning
confidence: 99%